Disaster Recovery Framework for Commercial Banks in Sri Lanka - Mueen Uddin; Sandun Hapugoda; Roop Chand Hindu (Journal of ICT Research and Applications, 2015)
The banking sector is the backbone of the entire financial economy of a country. In today's globalized world, most organizations use online transaction processing systems for transferring money and doing business. Natural or man-made disasters can lead to data loss which in turn can cause millions of dollars of money lost. This study focuses on disaster recovery practices in commercial banks in Sri Lanka. From our preliminary findings, it was concluded that commercial banks only have ad-hoc disaster recovery standards and practices, as there is no standard framework available. Fourteen (14) banks were selected for data collection and relevant authorities were interviewed. The results were translated as qualitative observations to understand the best practices. Similarly, international standards, compliance requirements of the central bank, and existing researches were used to develop a disaster recovery practice framework. The proposed framework was then validated for its efficiency and usefulness among commercial banks and found to be acceptable by the banking industry.